Enhancement of beta-carotene stability by encapsulation in high internal phase emulsions stabilized by modified starch and tannic acid. (December 2020) - Liu, Yikun; Yan, Chi; Chen, Jun; Wang, Yi; Liang, Ruihong; Zou, Liqiang; McClements, David Julian; Liu, Wei
Abstract: A new approach of fabricating temperature-responsive high internal phase emulsions (HIPEs) was established, based on controlling the hydrogen bonding in the system. These hydrogen bonds form between octenyl succinic anhydride modified starch (OSA-starch) and tannic acid (TA), as well as between the complexes of the two. The influence of system composition, pH, ionic strength, and temperature on the electrical, microstructural, and rheological properties of the HIPEs was determined. The HIPEs formed relatively firm gels at ambient temperature, but became considerably softer when heated above about 50 °C, which was attributed to weakening of the hydrogen bonds between the OSA-starch/TA complexes. The gels became firm again when cooled, which showed that they exhibited thermo-reversible rheological behavior. Encapsulation of β-carotene in HIPEs improved its chemical stability under UV-light exposure under all pH conditions. The edible HIPEs created in this study may therefore be useful where thermo-responsive gel-like systems are required. Graphical abstract: Image 1 Highlights: OSA-starch/Tannic acid complexes was used to stabilize the HIPEs. Tannic acid increased the viscosity and shear modulus of the HIPEs. HIPEs had temperature-responsive properties basing on hydrogen bonding interaction. HIPEs was able to protect β-carotene from photodegradation.